Analysis of the Effect of Open Unemployment Rate and Human Development Index on Poverty in North Sumatra Province - Riky Aulia Rachman Marpaung; Iin Sintia; Fitri Rahayu (Indonesian Journal of Advanced Research, 2023)
This study aims to determine the effect of the Open Unemployment Rate and the Human Development Index on poverty in North Sumatra. The data used is secondary data taken from BPS concerning the open unemployment rate, human development index and poverty percentage. Data obtained from panel data from 33 regencies/cities in North Sumatra for 3 years from 2020 to 2022. The data analysis technique uses regression analysis using Random Effect based on the results of the Lagrange Multiplier test. The results of the study show that the open unemployment rate has a negative and insignificant effect on poverty. Meanwhile, the human development index has a negative and significant effect on poverty in North Sumatra.